2022
DOI: 10.1017/s2040174422000344
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia-induced alterations in brain and liver gene expression and DNA methylation patterns in fetal mice

Abstract: Exposure to pregnancy complications, including preeclampsia (PE), has lifelong influences on offspring’s health. We have previously reported that experimental PE, induced in mice by administration of adenoviral sFlt1 at gestational day 8.5 combined with LPS at day 10.5, results in symmetrical growth restriction in female and asymmetrical growth restriction in male offspring. Here, we characterize the molecular phenotype of the fetal brain and liver with respect to gene transcription and DNA methylation at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Based on these findings, it is speculated that DNA methylation may play a role in mediating the increased risk of vascular disease later in life associated with PIH. Due to ethical constraints on human research, experimental animals were used to investigate the effects of maternal PIH on gene DNA methylation in multiple generations of offspring and its role in the occurrence of offspring diseases [ 197 , 198 ]. For instance, Guan et al [ 197 ] found that DNA hypomethylation of the G signaling gene in F1 sperm and F2 thoracic aorta, along with hyperactivation of downstream PI3K-Akt signaling, suggests that DNA methylation plays a crucial role in the development of hypertension in PIH offspring.…”
Section: Dna Methylation Changes In Pih Neonates and Childrenmentioning
confidence: 99%
“…Based on these findings, it is speculated that DNA methylation may play a role in mediating the increased risk of vascular disease later in life associated with PIH. Due to ethical constraints on human research, experimental animals were used to investigate the effects of maternal PIH on gene DNA methylation in multiple generations of offspring and its role in the occurrence of offspring diseases [ 197 , 198 ]. For instance, Guan et al [ 197 ] found that DNA hypomethylation of the G signaling gene in F1 sperm and F2 thoracic aorta, along with hyperactivation of downstream PI3K-Akt signaling, suggests that DNA methylation plays a crucial role in the development of hypertension in PIH offspring.…”
Section: Dna Methylation Changes In Pih Neonates and Childrenmentioning
confidence: 99%
“…Some animal studies have demonstrated a higher predisposition to cerebral complications in male than female offspring of preeclampsia. 61,62 A properly designed study to specifically analyze potential sexual dimorphism in the brain angiogenesis formation and function in offspring from preeclampsia is underway in our laboratory.…”
Section: Discussionmentioning
confidence: 99%